Pengaruh Perilaku & Komunikasi Terhadap Motivasi Berorganisasi: Studi Kasus Mahasiswa Universitas Buana Perjuangan Karawang - Nurmaulida, Dida; Raharjo, Dwi; Sidabutar, Hana Keziarani; Rofiqi, Munif; Wijaya, Muhammad Adhimawan (Jurnal Ilmiah Wahana Pendidikan, 2025)
The purpose of this study is to obtain empirical data on the influence of behavior and communication on organizational motivation. The method used is a survey method, which allows data collection from a large number of respondents to obtain a more comprehensive picture of the phenomenon being studied. This study has succeeded in identifying and analyzing several motivational factors that influence behavior and communication in student organizations in the Management study program at Buana Perjuangan University, Karawang